Detection of Reproductive Status in Ongole Crossbred (PO) Cow Based On Vaginal Epithel Morphology and Profile Hormone - Widyaningrum, Yeni; Aulanni'am, Aulanni'am; Marhendra, Agung Pramana Warih (Graduate School, Universitas Brawijaya, 2020)
Hormonal fluctuations in livestock will affect vaginal cytology good overview on the condition of estrous until pregnancy. The purpose of this study was to determine the physiological condition of Ongole crossbred (PO) cow during estrous and determine pregnancy by the description of vaginal epithelial cells, progesterone, and estrogen hormone profiles. The materials were used 35 cows with physiological status (estrous, 5th pregnancy period, 16th pregnancy period, 22nd pregnancy period, and 60th pregnancy period). Samples of Vaginal smear were stained with Giemsa, then it was observed using a microscope, with 40 times magnification. The progesterone and estrogen were analyzed by the ELISA method. The parameters measured were the percentage of vaginal epithelial cells, such as (parabasal, intermediate, and superficial) started estrous phase until the time of pregnancy in cows (5, 16, 22, and 60 days), hormone concentration, as well as the presence or absence of leukocytes. The result showed the Ongole crossbred cow estrous phase percentage of superficial cells 56.27%±6.49 higher than 26.23%±7.98 intermediate cells, followed by parabasal cells 17.50%±4.74. While in Ongole crossbred that were 5th pregnancy period until the 60th predominantly intermediate cell 80.43%±1.31, then the superficial cells 18.09%±1.30 and 1.48%±0.04 parabasal cells. Progesterone concentration was 63.74±1.07 ng.mL-1 in estrus cows, and steadily increased 93.71±0.94 ng.mL-1 to 149.5±0.71 ng.mL-1 in pregnant cows (5-60 days). The concentration of high estrogen levels were 122.38±0.63 ng.mL-1 in the estrous phase, then decreased 81.54±0.44 ng.mL-1 in the pregnancy phase. In conclusion, the concentration of hormone showed a diagnosis of pregnancy, which done by looking at changes in vaginal epithelial cells at the Ongole crossbred cow, and the cow estrous phase showed greater superficial cells compared by pregnant cows (5-60 days). Keywords: diagnosis of pregnancy, estrous, hormone, Ongole crossbred of cow, vaginal cytology.